Effectiveness of the cyclic administration of dienogest in a case of pathological disappearance of intestinal endometriosis - Tamura R; Tsuneki I; Yanase T (Dove Medical Press, 2013)
Ryo Tamura, Ikunosuke Tsuneki, Toru Yanase Department of Obstetrics and Gynecology, Niigata City General Hospital, Niigata, Japan Abstract: We have reported good control of atypical genital bleeding when using a cyclic administration of dienogest (repeated 4-week cycles, each consisting of the administration of 2 mg/day of dienogest for 3 weeks, followed by 1 week of drug withdrawal) in patients with endometriosis. Herein, we report the effectiveness of the long-term cyclic administration (22 months) of dienogest in a case of pathological disappearance of intestinal endometriosis diagnosed by endoscopy and histology of the lower gastrointestinal tract. There is no recurrent sign after 16 months of the treatment being stopped. Atypical genital bleeding during treatment was 3–5 days a month in each cycle. Compliance was good, so we could continue the therapy. The long-term cyclic administration of dienogest in patients with intestinal endometriosis may have significant merit. Keyword: atypical genital bleeding, dysmenorrhea, drug compliance, endoscopy, histology